Preparation and Characterization of Polymer TiO2 Nanocomposites via In-situ Polymerization - Lin, Feng (University of Waterloo, 2006)
Polymer nanocomposites are already a part of many important of worldwide businesses: automotive (molded part in cars), electronics and electrical engineering, household products, packaging industry, aircraft interiors, appliance components, security equipments. Among many nanocomposite precursors, TiO2 nanopowder is increasingly being investigated due to its special properties.
The objective of this work is to synthesize and characterize polymer-TiO2 hybrid nanocomposites. When dispersed at the nanoscale level TiO2 could act as visually transparent UV filters and high-thermomechanical-performance materials. The synthesis strategy involved two steps. Firstly, aggregated TiO2, as received, was modified by 3-trimethoxysilyl propylmethacrylate aimed at altering its surface characteristics. The effect of modifier concentration on changing the physicochemical properties of TiO2 surface was evaluated. Size distribution of unmodified and modified TiO2 nanopowders was measured using a particle size analyzer. The qualitative and quantitative grafting of vinyl groups on TiO2 surface was investigated with Fourier transform-infrared (FTIR) and proton nuclear magnetic resonance (1H-NMR) spectroscopy. Secondly, styrene monomer was then added to carry out copolymerization with vinyl groups on the modified TiO2 by free radical initiator 2,2-azobis isobutyronitrile (AIBN) in bulk medium. FTIR spectra confirmed the formation of nanocomposites with polystyrene chains chemically linked to the surface of TiO2 nanopowders. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated that the resulting nanocomposites displayed higher thermal stability and maintained similar glass transition temperatures (Tg) compared with pure PS. Ultraviolet ?visible spectroscopy (UV-Vis) investigated that these nanocomposites have improved optical properties potentially acting as visually transparent UV filters. Such incremented properties were attributed to the nancoscale dispersion (20-50nm size) of TiO2 into polystyrene matrix, which morphology was observed by scanning electron microscopy (SEM).
Keywords: Chemical Engineering; Nanocomposites; polymer; TiO2